Treatment Response in Association with Adherence Patterns to Highly Active Antiretroviral Therapy in Pediatric Patients with Perinatally Acquired HIV Infection. (September 2014) - Malhotra, Amisha; Whitley-Williams, Patricia N.; Gaur, Sunanda; Petrova, Anna
Background: Assessment of longitudinal adherence patterns on virologic and immunologic responses to HAART in perinatally acquired HIV patients has not been studied. Methods: Perinatally infected pediatric HIV patients with adherence documented at least twice and corresponding viral load and T-cell (%) data measured during 2008-2009 were studied. Multiple adherence measures were utilized to identify patients with persistent adherence, nonadherence, or alteration of adherence. Virologic and immunologic outcomes were assessed. Results: Persistent adherence, nonadherence, and alteration of adherence to HAART were recorded in 41.9%, 8.1%, and 50.0% of 62 studied patients. Persistent adherence was associated with higher likelihood for persistent virologic suppression and lower risk for persistent virologic failure. Conclusion: Alteration of adherence to HAART is a significant predictor of persistent virologic failure and high viremia in perinatally infected HIV patients. Implementation of longitudinal adherence assessments may target patients with nonsustained adherence patterns and help decrease the risk for virologic failure and disease progression.